High-reliability single-component underfill adhesive, preparation method thereof and flip chip
By adjusting the ratio of epoxy resin and modified polyetheramine curing agent, a single-component underfill glue with low thermal expansion coefficient and modulus is prepared, which solves the cracking problem of chip packaging during temperature cycling and high-temperature storage, and improves the reliability of chip packaging.
Patent Information
- Application Number
- CN202510104065.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2045-01-23
AI Technical Summary
In the existing chip packaging technology, the difference in thermal expansion coefficient between silicon chips and printed circuit boards leads to prone to cracking during temperature cycling and high-temperature storage experiments, and high-modulus underfill glue may also cause chip cracking when the material cures and shrinks.
By adjusting the ratio between bisphenol A epoxy resin, the first epoxy resin and the modified polyetheramine curing agent, a high-reliability single-component underfill glue is prepared, including spherical silica, epoxy resin, modified polyetheramine curing agent and other components, reducing its thermal expansion coefficient and modulus, and improving the reliability of chip packaging.
The bottom filler is achieved in close contact with the chip under high and low temperature environments, reducing cracking problems caused by solder joint fatigue damage and material curing and shrinking, and improving the reliability of chip packaging.
Smart Images

Figure CN119529723A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of chip packaging technology, and specifically relates to a high-reliability single-component underfill adhesive, its preparation method, and flip-chip. Background Technology
[0002] With continuous technological advancements, chip packaging technology will continue to evolve towards higher integration, better heat dissipation, and higher reliability. However, the significant difference in thermal expansion coefficients between silicon chips and printed circuit boards leads to cracking during temperature cycling and high-temperature storage experiments. High-modulus underfill adhesives can reduce solder joint fatigue damage, but excessively high modulus can cause chip cracking due to material shrinkage during curing. Appropriate modulus can better address the mismatch between the chip and other components. Therefore, low-elongation-coefficient, low-modulus underfill adhesives can effectively protect the chip and improve its reliability.
[0003] In other words, how to provide a highly reliable single-component underfill adhesive, by adjusting the ratio between bisphenol A epoxy resin, first epoxy resin and modified polyetheramine curing agent, so that the underfill adhesive has a low coefficient of thermal expansion and modulus, thereby improving the reliability of chip packaging, is a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention
[0004] The purpose of this invention is to provide a highly reliable single-component underfill adhesive, its preparation method, and a flip chip, so as to solve at least one of the above-mentioned technical problems.
[0005] To achieve the above objectives, the first aspect of the present invention provides a highly reliable one-component underfill adhesive, wherein the underfill adhesive comprises the following components by weight percentage: 50%–60% spherical silica, 28%–32% epoxy resin, 13%–17% modified polyetheramine curing agent, 0.1%–0.2% carbon black, 0.3%–0.5% silane coupling agent, and 0.2%–0.4% adhesion promoter; wherein the epoxy resin is composed of bisphenol A epoxy resin and a first epoxy resin, the first epoxy resin being of type NANOPOX® E500 or NANOPOX® E470.
[0006] In the first aspect, the bisphenol A epoxy resin has a mass percentage of 15% to 16%, and the first epoxy resin has a mass percentage of 14% to 15%.
[0007] In the first aspect, the type of the bisphenol A epoxy resin includes at least one of E44, DER321, and DER324.
[0008] In the first aspect, the modified polyetheramine curing agent is prepared by heating and stirring the polyetheramine until it is uniform, then adding isooctyl acrylate dropwise to the polyetheramine, wherein the molar ratio of the polyetheramine to the isooctyl acrylate is 1:1, and continuing the reaction to obtain the modified polyetheramine curing agent.
[0009] In the first aspect, the modified polyetheramine curing agent has the following structural formula: .
[0010] In the first aspect, the particle size of the spherical silica is 0.5 to 5 μm.
[0011] In the first aspect, the adhesion promoter includes Adherant1121.
[0012] A second aspect of the present invention provides a method for preparing a high-reliability one-component underfill adhesive as described in the first aspect, the method comprising: S1. Add each component to the mixing cup according to its respective mass percentage, and mix evenly using a first centrifugal mixer to obtain a first slurry; the mass percentage of each component specifically includes: 50%–60% spherical silica, 28%–32% epoxy resin, 13%–17% modified polyetheramine curing agent, 0.1%–0.2% carbon black, 0.3%–0.5% silane coupling agent, and 0.2%–0.4% adhesion promoter; S2. The first slurry is transferred to a three-roll mill for dispersion treatment to obtain a uniformly dispersed second slurry; S3. The second slurry is vacuum degassed using a second centrifugal mixer to obtain a bottom filler adhesive.
[0013] In the second aspect, the operating parameters of the first centrifugal mixer include: a mixing time of 50–75 s, a rotation of 800 r / min, and a revolution of 1000 r / min; the operating parameters of the three-roll mill include: a feed gap of 20–35 μm and a discharge gap of 10–15 μm; the operating parameters of the second centrifugal mixer include: a vacuum degassing time of 55–70 s, a rotation of 100 r / min, and a revolution of 1000 r / min.
[0014] A third aspect of the present invention provides a flip chip having a packaging structure comprising a material formed by curing the high-reliability single-component underfill adhesive described in the first aspect.
[0015] Beneficial effects: This invention provides a high-reliability one-component underfill adhesive, comprising the following components by weight percentage: 50%–60% spherical silica, 28%–32% epoxy resin, 13%–17% modified polyetheramine curing agent, 0.1%–0.2% carbon black, 0.3%–0.5% silane coupling agent, and 0.2%–0.4% adhesion promoter; the epoxy resin is composed of bisphenol A epoxy resin and a first epoxy resin, wherein the first epoxy resin is of type NANOPOX® E500 or NANOP. OX®E470 uses a first epoxy resin containing a small amount of nano-silica and a bisphenol A epoxy resin as the base resin to provide adhesive and mechanical properties for the underfill adhesive. Combined with micron-sized spherical silica, it effectively reduces the coefficient of thermal expansion of the underfill adhesive. A modified polyetheramine curing agent with a branched structure is used to crosslink with the base resin, reducing the modulus of the underfill adhesive. Simultaneously, a small amount of silane coupling agent improves the adhesion between the underfill adhesive and the substrate / chip, thereby improving the reliability of chip packaging. This invention controls the coefficient of thermal expansion and storage modulus of the underfill adhesive by adjusting the ratio of the first epoxy resin, bisphenol A epoxy resin, and modified polyetheramine curing agent, ensuring that the underfill adhesive maintains tight contact with the chip under long-term high and low temperature environments, thus improving the reliability of chip packaging. Attached Figure Description
[0016] To more clearly illustrate the technical solutions in the embodiments of this specification or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0017] Figure 1 This is a flowchart of a method for preparing a highly reliable single-component underfill adhesive according to the present invention. Detailed Implementation
[0018] The present invention will be described in detail below with reference to specific embodiments and examples, thereby making the advantages and various effects of the present invention more clearly apparent. Those skilled in the art should understand that these specific embodiments and examples are for illustrative purposes only and are not intended to limit the present invention.
[0019] Throughout this specification, unless otherwise specified, the terminology used herein should be understood as having the meaning commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. In the event of any conflict, this specification shall prevail.
[0020] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be obtained by purchasing them from the market or by existing methods.
[0021] This application provides a high-reliability one-component underfill adhesive, which comprises the following components by weight percentage: 50%–60% spherical silica, 28%–32% epoxy resin, 13%–17% modified polyetheramine curing agent, 0.1%–0.2% carbon black, 0.3%–0.5% silane coupling agent, and 0.2%–0.4% adhesion promoter; the epoxy resin is composed of bisphenol A epoxy resin and a first epoxy resin, wherein the first epoxy resin is of type NANOPOX® E500 or NANOPOX® E470.
[0022] Specifically, the present invention provides a high-reliability single-component underfill adhesive, comprising the following components by weight percentage: 50%–60% spherical silica, 28%–32% epoxy resin, 13%–17% modified polyetheramine curing agent, 0.1%–0.2% carbon black, 0.3%–0.5% silane coupling agent, and 0.2%–0.4% adhesion promoter; the epoxy resin is composed of bisphenol A epoxy resin and a first epoxy resin, wherein the first epoxy resin is of type NANOPOX® E500 or NAN OPOX® E470 uses a first epoxy resin containing a small amount of nano-silica and a bisphenol A epoxy resin as the base resin to provide adhesive and mechanical properties for the underfill adhesive. Combined with micron-sized spherical silica, it effectively reduces the coefficient of thermal expansion of the underfill adhesive. A modified polyetheramine curing agent with a branched structure is used to crosslink with the base resin, reducing the modulus of the underfill adhesive. Simultaneously, a small amount of silane coupling agent improves the adhesion between the underfill adhesive and the substrate / chip, thereby improving the reliability of chip packaging. This invention controls the coefficient of thermal expansion and storage modulus of the underfill adhesive by adjusting the ratio of the first epoxy resin, bisphenol A epoxy resin, and modified polyetheramine curing agent, ensuring that the underfill adhesive maintains tight contact with the chip under long-term high and low temperature environments, thus improving the reliability of chip packaging.
[0023] In some possible embodiments, the bisphenol A epoxy resin has a mass percentage of 15% to 16%, and the first epoxy resin has a mass percentage of 14% to 15%.
[0024] In some possible embodiments, the type of the bisphenol A epoxy resin includes at least one of E44, DER321, and DER324.
[0025] First epoxy resins NANOPOX® E500 and NANOPOX® E470 are high-performance nanosphere silica particles uniformly dispersed in epoxy resin. Through synthesis and surface modification, the silica spherical particles in the products have a very small particle size (about 20 nm) and an extremely narrow particle size distribution. When mixed with bisphenol A epoxy resin, they can be used as a matrix resin to provide basic adhesive and mechanical properties.
[0026] In some possible embodiments, the modified polyetheramine curing agent is prepared by heating and stirring the polyetheramine until it is uniform, then adding isooctyl acrylate dropwise to the polyetheramine, wherein the molar ratio of the polyetheramine to the isooctyl acrylate is 1:1, and continuing the reaction to obtain the modified polyetheramine curing agent.
[0027] In some possible embodiments, the modified polyetheramine curing agent has the following structural formula: This invention utilizes isooctyl acrylate to modify the conventional curing agent polyetheramine, resulting in a modified polyetheramine curing agent with a branched structure. The branched structure is embedded in the crosslinking network during the crosslinking process between the modified polyetheramine curing agent and epoxy resin, causing phase separation and forming a two-phase mesh structure with alternating dense and loose phases. This reduces the internal stress in the underfill adhesive, achieving the effects of toughening and reducing mold density. In a specific embodiment, 200g of polyetheramine D230 is added to a three-necked flask and stirred evenly in a constant-temperature water bath. Isooctyl acrylate is then added dropwise at a molar ratio of 1:1 to polyetheramine. The reaction is allowed to proceed for 3.5 hours, with the stirring speed adjusted according to the reaction progress to ensure smooth reaction, thereby obtaining the modified polyetheramine curing agent with a branched structure.
[0028] In some possible embodiments, the particle size of the spherical silica is 0.5–5 μm.
[0029] This is because using spherical silica as a filler material can not only reduce the thermal expansion coefficient and hygroscopicity of the underfill adhesive, but also increase the modulus of the underfill adhesive. The particle size of the spherical silica is selected to be 0.5 to 5 μm, which can be uniformly dispersed in the matrix resin and can interact with the nano silica in the first epoxy resin to improve the encapsulation effect of the underfill adhesive.
[0030] In some possible embodiments, the adhesion promoter includes Adherant1121.
[0031] This invention improves the connection between the underfill adhesive and the substrate, the SiO2 or Si3N4 passivation layer on the chip surface, and enhances the adhesion strength between the underfill adhesive and the substrate surface by using adhesion promoters and silane coupling agents, thereby improving the encapsulation performance of the underfill adhesive.
[0032] Based on a general inventive concept, please refer to... Figure 1 This application also provides a method for preparing a high-reliability one-component underfill adhesive as described in the first aspect, the method comprising: S1. Add each component to the mixing cup according to its respective mass percentage, and mix evenly using a first centrifugal mixer to obtain a first slurry; the mass percentage of each component specifically includes: 50%–60% spherical silica, 28%–32% epoxy resin, 13%–17% modified polyetheramine curing agent, 0.1%–0.2% carbon black, 0.3%–0.5% silane coupling agent, and 0.2%–0.4% adhesion promoter; wherein, the operating parameters of the first centrifugal mixer include: mixing time of 50–75 s, rotation of 800 r / min, and revolution of 1000 r / min; S2. The first slurry is transferred to a three-roll mill for dispersion treatment to obtain a uniformly dispersed second slurry; wherein, the operating parameters of the three-roll mill include: feed gap of 20-35 μm and discharge gap of 10-15 μm; S3. The second slurry is vacuum degassed using a second centrifugal mixer to obtain a bottom filler adhesive. The operating parameters of the second centrifugal mixer include: vacuum degassed time of 55-70s, rotation of 100r / min, and revolution of 1000r / min.
[0033] Based on a general inventive concept, a third aspect of the present invention provides a flip chip having a packaging structure comprising a material formed by curing the high-reliability single-component underfill adhesive described in the first aspect.
[0034] The present application is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the application. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national standards. If there is no corresponding national standard, then general international standards, conventional conditions, or conditions recommended by the manufacturer are followed.
[0035] The components of the raw materials in Comparative Examples 1-4 and Examples 1-3, expressed as a percentage by mass, are shown in Table 1 below: Table 1. Distribution ratio of each raw material group The underfill adhesives provided in Examples 1-3 and Comparative Examples 1-4 were subjected to tests on viscosity, flowability, storage modulus, and coefficient of thermal expansion, as well as high-temperature storage tests, high-low temperature cycling tests, and temperature and humidity-free high-acceleration stress tests. The specific test procedures are as follows: 1. Flowability test method: A 15 mm wide, 20 mm long, and 0.5 mm thick Si wafer with copper pillars is attached to the substrate with 50 μm thick double-sided tape at the four corners. The bottom filler to be tested is applied horizontally (35-40) mg along one side of the square Si wafer using a dispensing machine. The wafer is placed on a 110°C hot plate and timing is started at the same time. Under the action of capillary force, the bottom filler will flow at the bottom of the Si wafer. The time it takes for the filler to fully flow is recorded. 2. Storage modulus test method: Reference standard: ASTM E2254-2018. Take a fully cured sample and prepare the test sample with a size of 55mm×10mm×3mm. Measurement mode: dual cantilever mode, vibration frequency: 1Hz, amplitude: 10μm, heating rate: 5℃ / min. 3. Thermal expansion coefficient test method: Reference standard: ASTM E831-2019. Take a sample that has been fully cured at 165℃ for 2 hours. Prepare the test sample with dimensions of 5mm×5mm×2mm. Test the thermal expansion coefficient and glass transition temperature (TMA) of the sample using TMA (compression mode). TMA parameter settings: Preload force: 0.05N, first scan: room temperature - 260℃ (heating rate 10℃ / min), second scan: room temperature - 260℃ (heating rate 5℃ / min). Take the curve data of the second heating segment. 4. High Temperature Storage Test (HTST): The filled silicon wafer is completely cured and kept at 150°C for 1000 hours. The condition of the silicon wafer is then observed. 5. High and low temperature cycling test (TCT): The filled silicon wafer is completely cured and cycled 1000 times at a temperature of -55 to 125℃. The integrity of the silicon wafer is then observed. 6. Temperature and Humidity Unbiased High Accelerated Stress Test (uHAST): The sample is poured into a pudding mold with a diameter of 3 mm and a height of 2 mm. One end of the poured sample is in contact with the silicon wafer. The silicon wafer is fixed to the pudding mold. After curing at 165℃ for 2 hours, the pudding mold is removed, the sample is taken out, and a thrust tester is used. The test is carried out at 130℃ and 85%RH for 96 hours. After removal, the sample is tested with a thrust tester. The thrust tester speed is 50 μm / s, and the contact height is 20 μm.
[0036] The test results are shown in Table 2 below: Table 2 Test Results As can be seen from the table above: (1) In Comparative Example 1, epoxy resin E470 or E500 was not used. During high temperature storage test and high and low temperature cycle test, the bottom filler glue and silicon wafer were prone to cracking, which affected the chip packaging performance. (2) Comparative Example 2 uses conventional curing agent D230. The bottom filler prepared has a large energy storage modulus. However, during the high temperature storage test and high and low temperature cycling test, the bottom filler is prone to cracking with the silicon wafer, which affects the chip packaging performance. (3) Although Comparative Examples 3-4 used modified polyetheramine curing agent and epoxy resin E470 / E500, the amount added was not within the range specified in this application. The prepared bottom filler would still crack with the silicon wafer during the high temperature storage test and high and low temperature cycling test, affecting the chip packaging performance. (4) The raw material formulations used in Examples 1-3 are all within the formulation ratio specified in this application. The prepared bottom filler has a low coefficient of thermal expansion and a suitable energy storage modulus. It can still be in close contact with the silicon wafer during high temperature storage test and high and low temperature cycling test, thus ensuring the reliability of chip packaging.
[0037] In summary, by using the underfill adhesive formulated within the specified range of this application, and adjusting the ratio between bisphenol A epoxy resin, the first epoxy resin, and the modified polyetheramine curing agent within a fixed range, an underfill adhesive with good flowability, low coefficient of thermal expansion, and low modulus can be obtained, and the reliability of the underfill adhesive encapsulating the chip can be maintained at high and low temperatures.
[0038] Finally, it should be noted that the terms “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0039] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including both the preferred embodiments and all changes and modifications falling within the scope of the invention.
[0040] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.
Claims
1. A high reliability single component bottom filler, characterized in that: The bottom filling glue includes the following components by mass percentage: 50% to 60% spherical silica, 28% to 32% epoxy resin, 13% to 17% modified polyether amine curing agent, 0.1% to 0.2% carbon black, 0.3% to 0.5% silane coupling agent, and 0.2% to 0.4% adhesion promoter; the epoxy resin is composed of bisphenol A epoxy resin and a first epoxy resin, and the model of the first epoxy resin is NANOPOX®E500 or NANOPOX®E470.
2. The high reliability one-component bottom filling adhesive according to claim 1, characterized in that: The mass percentage of the bisphenol A epoxy resin is 15% to 16%, and the mass percentage of the first epoxy resin is 14% to 15%.
3. The high reliability one-component bottom filling adhesive according to claim 2, characterized in that: The type of the bisphenol A epoxy resin includes at least one of E44, DER321 and DER324.
4. The high reliability one-component bottom filling adhesive according to claim 3, characterized in that: The modified polyetheramine curing agent is prepared by the following method: heating and stirring the polyetheramine, after stirring evenly, adding isooctyl acrylate dropwise into the polyetheramine, wherein the molar ratio of the polyetheramine to the isooctyl acrylate is 1:1, and continuing the reaction to obtain the modified polyetheramine curing agent.
5. The high reliability one-component bottom filling adhesive according to claim 4, characterized in that: The structural formula of the modified polyetheramine curing agent is: 。 6. The high reliability one-component bottom filling adhesive according to claim 5, characterized in that: The particle size of the spherical silicon dioxide is 0.5 to 5 μm.
7. The high reliability one-component bottom filling adhesive according to claim 6, characterized in that: The adhesion promoter includes Adherant1121.
8. A method for preparing a high-reliability single-component underfill adhesive as claimed in any one of claims 1 to 7, characterized in that: The preparation method comprises: S1. Add each component into a stirring cup according to their respective mass percentages, and mix them evenly by a first centrifugal stirrer to obtain a first slurry; the mass percentages of the components specifically include: 50% to 60% spherical silica, 28% to 32% epoxy resin, 13% to 17% modified polyether amine curing agent, 0.1% to 0.2% carbon black, 0.3% to 0.5% silane coupling agent, and 0.2% to 0.4% adhesion promoter; S2, transferring the first slurry to a three-roll mill for dispersion treatment to obtain a uniformly dispersed second slurry; S3. Vacuum degassing the second slurry using a second centrifugal mixer to obtain a bottom filling adhesive.
9. The method for preparing a high-reliability one-component underfill according to claim 8, characterized in that: The working parameters of the first centrifugal mixer include: stirring time of 50 to 75 seconds, rotation of 800 r / min, revolution of 1000 r / min; The working parameters of the three-roll mill include: the feed gap is 20-35 μm, the discharge gap is 10-15 μm; The working parameters of the second centrifugal mixer include: vacuum degassing time of 55 to 70 seconds, rotation of 100 r / min, and revolution of 1000 r / min.
10. A flip chip, characterized in that: The flip chip has a packaging structure, and the packaging structure includes a material formed by curing the high-reliability single-component bottom filling glue according to any one of claims 1 to 7.
Citation Information
Patent Citations
Single-component underfill adhesive and preparation method thereof
CN112048271A
Underfill adhesive
CN112724899A
Epoxy underfill adhesive and preparation method thereof
CN117701213A
Underfill adhesive with low thermal expansion coefficient, preparation method thereof and chip packaging structure
CN117801745A
High-fluidity underfill adhesive, preparation method thereof and flip chip
CN118772819A
Cited By
Solvent-free printing state film sealing adhesive, preparation method thereof and chip packaging method
CN120248777A
Bottom filling adhesive for packaging large-size chip, preparation method of bottom filling adhesive and packaging structure
CN120795851A
A filler-free high-humidity-heat-reliability low-viscosity underfill adhesive composition, a preparation method and application thereof
CN122854992A
